The Philippine Public Transportation Heritage Museum - Bremer, Timothy Dustin G. (College of Architecture, University of the Philippines Diliman, 2025)
Public transportation plays an integral role in the socio-economic and socio-cultural fabrics of society. In recent years, the urban transport landscape of the Philippines has seen developments that have caused drastic changes. This inevitable phenomenon inspired this comprehensive design project, which aims to preserve the public transportation heritage of the Philippines whilst fostering public appreciation, cultivating innovation and progress, and raising awareness on tis urban transport landscape. It utilized the qualitative approach in its research methodology by conducting historical research, case studies, observational research, and interviews. On the other hand, it utilized the pragmatic approach in its design methodology when formulating the site analysis, user analysis, spatial analysis, and the conceptual design. Its design objectives include: to establish an organized curatorial layout, to create a comprehensive experience for museum visitors, and to embody the Filipino identity. The Philippine Public Transportation Heritage Museum consists of a festive museum building that house multiple galleries, featuring kalesas, tricycles, tranvias, buses, jeepneys, and other innovative vehicles, as well as a high-end parking facility that features a silo automated parking system. Ultimately, this project would inspire an urban transport landscape for the Philippines that is not only progressive, but also grounded in the country's cultural identity.